2017
DOI: 10.1016/j.bjid.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of Southern Hemisphere inactivated quadrivalent influenza vaccine: a Phase III, open-label study of adults in Brazil

Abstract: The World Health Organization influenza forecast now includes an influenza B strain from each of the influenza B lineages (B/Yamagata and B/Victoria) for inclusion in seasonal influenza vaccines. Traditional trivalent influenza vaccines include an influenza B strain from one lineage, but because two influenza B lineages frequently co-circulate, the effectiveness of trivalent vaccines may be reduced in seasons of influenza B vaccine-mismatch. Thus, quadrivalent vaccines may potentially reduce the burden of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Both IBV Victoria and Yamagata were recently reported to co‐circulate in many regions over the globe, therefore constant surveillance is important when choosing a vaccine. In this study, a low rate of vaccination was observed among IBV‐infected patients; also, vaccinal mismatch should not be disregarded as an explanation for the fact that approximately 25% of the hospitalized patients with SARI had received the flu vaccine and, still, were infected with IBV—probably of a lineage not present in the annual vaccine composition 26 . The estimated rate of vaccinal mismatch reported in previous studies can be >91% in Brazil and 52% in South America 26 …”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Both IBV Victoria and Yamagata were recently reported to co‐circulate in many regions over the globe, therefore constant surveillance is important when choosing a vaccine. In this study, a low rate of vaccination was observed among IBV‐infected patients; also, vaccinal mismatch should not be disregarded as an explanation for the fact that approximately 25% of the hospitalized patients with SARI had received the flu vaccine and, still, were infected with IBV—probably of a lineage not present in the annual vaccine composition 26 . The estimated rate of vaccinal mismatch reported in previous studies can be >91% in Brazil and 52% in South America 26 …”
Section: Discussionmentioning
confidence: 59%
“…In this study, a low rate of vaccination was observed among IBV-infected patients; also, vaccinal mismatch should not be disregarded as an explanation for the fact that approximately 25% of the hospitalized patients with SARI had received the flu vaccine and, still, were infected with IBV-probably of a lineage not present in the annual vaccine composition. 26 The estimated rate of vaccinal mismatch reported in previous studies can be >91% in Brazil and 52% in South America. 26 The main limitation of this study was the lack of data, which occurred because the notification systems changed along the period; therefore, some data was only available for a limited number of cases, and some variables had missing values.…”
Section: This Study Analyzed Cases Of Ibv Infection Over 17 Years In Riomentioning
confidence: 94%
“…This is not unexpected given the tendency for older adults to have high baseline HI antibody titers, arising from either natural exposure to influenza or previous vaccinations, which have been reported to reduce antibody responses to subsequent seasonal influenza vaccination [18–20]. In populations with high prevaccination SPRs, such as those seen in our study, it is difficult to demonstrate an improved immune response based on SCRs alone [21]. In addition, the immune responses to influenza vaccines are often less robust in older adults owing to immunosenescence [22–24].…”
Section: Discussionmentioning
confidence: 65%
“…The reason for this may be a sharp decrease in anti-HI titers against vaccine strains after 12 months following influenza vaccination, which has been observed in people with obesity [ 6 ]. The post-vaccination GMT were also lower in studied subjects compared to the general adult population [ 26 28 , 32 34 ]. However, it cannot be excluded that differences in GMT levels described in the literature likely reflect, at least in part, the inter-laboratory discrepancies in titer measurements.…”
Section: Discussionmentioning
confidence: 99%